Loan-Address Terms to Enhance Atmosphere of Source Novel in Target Novel - Ester Jakindo; Ilza Mayuni; Yumna Rasyid (Humaniora, 2018)
The objective of this research was to analyze how English address terms in “The Princess Diaries” were translated into Indonesian in “Buku Harian Sang Putri”, which published eight times that might indicate its popularity among Indonesian enthusiasts. This research applied content analysis method, particularly the theory of address terms postulated by Braun and Kridalaksana also the theory of translation strategies proposed by Baker, Newmark, and Vinay and Darbelnet. The data were both target and source address terms in dialogs. The address terms were grouped into subsets of the unit for analysis. The result shows English address terms are translated into 11 Indonesian address terms and ’konstruksi kepemilikan’ by using ten translation strategies. The research also shows that loan-address terms (full-loan and scattered-address terms) are chosen as a strategy to enhance the novel’s source atmosphere though they distort the target culture to some extent. To conclude, address terms aren’t always translated into address terms and pragmatic meaning’s distortion happens though various translation strategies are applied. It is necessary to conduct research on how to minimize loan address terms to maintain the source novel’s atmosphere without distorting the pragmatic meaning of Indonesian culture.